Comparison of the Effectiveness of the Approach of Schema Therapy with Treatment Based on Acceptance and Commitment on Emotional Intelligence of Married Men and Women with Extramarital Relationship - Beheshti Moghaddam, Elmira; Madahi, Mohammad Ebrahim; Jafari Roshan, Marjan; Ghodsi, Parvaneh (Applied Family Therapy Journal (AFTJ), 2023)
Aim: This research was conducted with the aim of comparing the effectiveness of the schema therapy approach with the therapy based on acceptance and commitment on the emotional intelligence of married women and men with extramarital relationships. Methods: The current research was an applied research and in terms of the research method, it was non-descriptive and quasi-experimental with a pre-test-post-test design and follow-up with a control group. The current research population included married men and women with extramarital relationship who referred to four counseling and psychological clinics in Tehran in 12 months of 2019 and 9 months of 2014 due to marital disputes with their spouses and the disclosure of their extramarital relationship. Among the couples, 45 couples were randomly selected (23 women and 22 men who committed extramarital relations). The criteria for inclusion in the research included: being married, not pregnant, at least 25 and at most 60 years old, having minimal literacy, not having an acute psychological illness or problem, and registering written informed consent to participate in therapy sessions. In this research, the subjects were placed in three groups of Young’s (2003) schema therapy test, acceptance and commitment based test, and control test, and before and after the intervention, they completed Bar-On's (2000) emotional intelligence questionnaire. Data were analyzed using repeated measure variance. Results: The results showed that the intervention of the experimental schema therapy group (F=6.66, P=0.020) and the group based on acceptance and commitment (F=6.10, P=0.024) on emotional intelligence in the post stage The test is effective and this effect was stable in the follow-up phase; Also, based on the results of Tukey's post hoc test, there is no significant difference between the two groups of schema therapy approach and acceptance and commitment on emotional intelligence in terms of effectiveness. Conclusion: According to the obtained results, the approach of schema therapy and therapy based on acceptance and commitment is an effective approach to increase the emotional intelligence of married women and men with extramarital relationships.